Equatorial TEC variations during the Geomagnetic Storm of July 15–17, 2000 - Ho, Yih Hwa; Zain, A.F.M; Abdullah, M; Ramli, A.B; Hassan, W.S.W (2002)
This paper studies the Malaysian ionospheric response to the major geomagnetic storm during July 15-17, 2000, using nationwide network of GPS receivers. In this study we focus on the relative variations in TEC at Malaysia region with respect to a quiet period. Results indicate that the relative variations in TEC are variable during the storm time rangingabout –20 to 25%. There were positive phase exceeds 25% TECenhancement during the main phase of the storm.However there is clearly negative phaseduring the recovery phase of the storm, whose change ratio exceeds –20% TEC depression.